Cancer/testis antigens FBXO39 and CEP55 expression correlates with survival in GBM patients - Parisa Azimi; Maryam Bazrgar; Taravat Yazdanian; Mehdi Totonchi; Abolhassan Ahmadiani (PLoS ONE, 2025)
Background Glioblastoma multiform (GBM) is a primary brain malignancy resistant to conventional therapies, with poor survival. Cancer testis antigens (CTAs) are important cancer diagnostic biomarkers and therapeutic targets. Bioinformatics analysis of GBM clinical and molecular data was undertaken to identify and validate the key CTA genes, whose expression correlates with the survival of GBM patients. Methods RNA-seq data of GBM were downloaded from TCGA and CGGA databases to analyze differentially expressed genes (DEGs). Cancer Testis genes (from the CT database), found up and down-regulated in the GBM series compared to normal samples, were determined in both TCGA and CGGA databases. Overall survival (OS) of GBM patients in the TCGA and CGGA databases as a function of the expression of key CTA genes was considered to identify those whose expression significantly predicts patient survival. The predictive values of our candidate genes were then tested using our independent cohort (n = 29) using an RT-qPCR approach. Results Compared to normal brain samples, a total of 2463 and, 6249 up- and 3706 and, 6606 down-regulated genes were found in the TCGA and CGGA, respectively. The intersection between 279 CTAs in the CD database and the up-and-down-regulated genes of both other databases was found in 11 and 8 CTAs, respectively. Using tumor samples from our cohort of 29 patients and an RT-qPCR approach, we found that FBXO39 and CEP55 genes were highly expressed in GBM and that their expression predicted the OS (P < 0.05). Conclusions Our results support the potential use of FBXO39 and CEP55 gene expression measurement as prognostic biomarkers in GBM patients.